Advances in nanostructured homojunction solar cells and photovoltaic materials. (1st March 2020) - Ali, Nisar; Ahmed, R.; Luo, Jing Ting; Wang, Mingkui; Kalam, Abul; Al-Sehemi, Abdullah G.; Fu, Yong Qing
Abstract: Recently, various materials have been explored for their potential applications in homojunction solar cells, which have distinct advantages of good lattice matching at the junction interfaces with minimum recombination losses of carriers. This paper presents an overview of design, technique, and materials in the advanced homojunction solar cells with their latest reported efficiencies. We review the development of homojunction solar cells with two-dimensional (or thin film) based materials, one-dimensional materials (nanowire/nanorods/nanotube), and zero-dimensional (nanodots and quantum dots) based materials. Among the thin film materials explored for homojunction solar cells, we mainly focus this review on CuInS2, InGaN, and InP based homojunction solar cells.